Quality of colonoscopy in Lynch syndrome - Niv, Yaron; Moeslein, Gabriela; Vasen, Hans F.A.; Karner-Hanusch, Judith; Lubinsky, Jan; Gasche, Christoph; The MesaCAPP Research Group (Endoscopy International Open, 2014)
Lynch syndrome (LS) accounts for 2 – 4 % of all colorectal cancers. Affected family members have a germline mutation in one of the DNA mismatch repair genes MLH1, PMS2, MSH2, or MSH6, and a lifetime risk for development of colorectal cancer of 25 – 75 %. Current guidelines recommend annual to biannual surveillance colonoscopy in mutation carriers. Several factors may predict failure to prevent interval cancer in LS: more lesions in the right colon; more flat (“non polypoid”) and lateral growing polyps; small adenomas may already harbor high grade dysplasia or a high percentage of villous component and become advanced adenomas; there is a short duration of the adenoma – carcinoma sequence; synchronous lesions have high prevalence; patients are younger and less tolerant to colonoscopy (need more sedation); and repeated colonoscopies are needed for lifelong surveillance (patient experience is important for compliance). In order to prevent cancer in LS patients, surveillance colonoscopy should be performed in an endoscopic unit experienced with LS, every 1 – 2 years, starting at age 20 – 25 years, or 10 years younger than the age of first diagnosis in the family (whichever is first), and yearly after the age of 40 years. Colonoscopy in LS patients should be a very meticulous and precise procedure (i. e. taking sufficient withdrawal time, documentation of such warranted), with removal of all of the polyps, special attention to the right colon and alertness to flat lesions. Following quality indicators such as successful cleansing of the colon and removal of every polyp will probably improve prevention of interval cancers. At this moment, none of the new endoscopic techniques have shown convincing superiority over conventional high resolution white light colonoscopy.